Wanprestasi Perjanjian Kerja PT Perkebunan Nusantara II Medan dengan Pensiunan Karyawan - Nur Hidayah; Tetty Marlina Tarigan (UNES Law Review, 2023)
This article is entitled Default of PT Perkebunan Nusantara II Medan with retired employees of PT Perkebunan Nusantara II Medan. The work agreement made and agreed upon by PT Perkebunan Nusantara II Medan with retired employees is that as long as the company has not provided old age compensation, then retired employees are still entitled to occupy official employee housing. However, the company did not comply with the work agreement that had been agreed and stipulated, PT Perkebunan Nusantara II Medan issued a summons three times to evict the retirees from the company's official housing land before giving old age compensation to retired employees, and only giving compensation money. to retired employees. The aim of this research is to explain the forms of default committed by PT Perkebunan Nusantara II Medan, and efforts to resolve breaches of employment agreements between the company and retired employees. The method used in this research is an empirical juridical method which comes from primary legal material sources by examining statutory regulations related to this research. The results of this research found that there were defaults committed by the company with efforts to resolve the default through non-litigation channels between the company and retired employees, by fulfilling the obligations and achievements that should have been fulfilled by the company.